IV DripAssist: An Innovative Way to Monitor Intravenous Infusions Away From an Outlet?. (21st March 2019) - Couperus, Kyle; Kmiecik, Karl; Kang, Christopher
Abstract: Intravenous (IV) administration of fluids and medications are a significant part of patient treatment. In austere environments, typical methods of counting drops from gravity drips or infusion pumps both have limitations such as accuracy, weight, and need for power. The DripAssist device calculates drip rates by counting drops in IV tubing drip chambers and may provide a useful patient safety monitor adjunct. The protocol was IRB approved, prospective, and designed as a pilot study involving 28 Madigan Army Medical Center Emergency Department personnel. After a brief didactic introduction to the device for clinical staff with no prior experience using the device, participants were timed setting three normal saline infusions at rates of 250 mL/h, 125 mL/h and 83 mL/h with 15gtt/mL tubing. Participants filled out a survey on perceived ease of use and utility of the device compared to pumps and manual counting. Most participants felt the DripAssist device was easy to understand and set up, but nurses and physician assistants were more likely than medics to perceive a benefit versus IV pumps or gravity drips. The DripAssist device may offer a safe, low-weight, functional tool which could improve care in a variety of resource-limited environments. However, additional studies using the device during actual field exercises would be beneficial.